Health Education About Stroke Patient Treatment Of Knowledge And Family Anxiety - Sriwana (Chakra Brahmanda Lentera Institute, 2019)
Stroke is still the main cause of disability. The impact of a stroke greatly depends on the location and extent of the damage, and age. Patient motivation and support from the family is very important to increase self-confidence to treat patients after stroke. If the family cannot treat stroke patients, then the family can experience anxiety and have an impact on the health of stroke patients. Objective To find out whether there is an influence of health education on the care of stroke patients on family knowledge and anxiety in Mokoyurli District General Hospital, Buol District. The design used in this research is pre-experiment. The population is all families with stroke patients. The sample size was 32 respondents using simple random sampling technique. The independent variable of research is health education. The dependent variable is Knowledge and anxiety. Data were collected using a questionnaire, then data were analyzed using Wilcoxon test with a significance level of α ≤ 0.05. The results showed that almost half the respondents had less knowledge before the intervention as many as 15 respondents (46.9%), good knowledge after the intervention were 19 respondents (59.4%), anxiety who were before the intervention were 17 respondents (53.1 %), mild anxiety after the intervention were 17 respondents (53.1%). Wilcoxon statistical test there is an influence of health education about the care of stroke patients on family knowledge, Wilcoxon statistical test there is an effect of health education about care of stroke patients on family anxiety. There is an Influence of Health Education on Stroke Patient Care on Family Knowledge and Anxiety in the Mokoyurli District General Hospital, Buol District.